The Curcumin Analogs 2-Pyridyl Cyclohexanone Induce Apoptosis via Inhibition of the JAK2–STAT3 Pathway in Human Esophageal Squamous Cell Carcinoma Cells - Wang, Ying; Zhou, Pengjun; Qin, Shurong; Xu, Dandan; Liu, Yukun; Fu, Wuyu; Ruan, Bibo; Zhang, Li; Zhang, Yi; Wang, Xiao; Pan, Yuwei; Wang, Sheng; et al. (Frontiers in Pharmacology, 2018)
Multiple modifications to the structure of curcumin have been investigated with an aim to improve its potency and biochemical properties. Previously, we have synthesized a series of curcumin analogs. In the present study, the anticancer effect of 2-pyridyl cyclohexanone, one of the curcumin analogs, on esophageal carcinoma Eca109 and EC9706 cell lines and its molecular mechanisms were investigated. 2-pyridyl cyclohexanone inhibited the proliferation of Eca109 and EC9706 cells by inducing apoptosis as indicated by morphological changes, membrane phospholipid phosphatidylserine ectropion, caspase 3 activation and cleavage of PARP. Mechanistic studies indicated that 2-pyridyl cyclohexanone disrupted mitochondrial membrane potential, disturbed the balance of the Bcl-2 family proteins, and triggered apoptosis via the mitochondria-mediated intrinsic pathway. In 2-pyridine cyclohexanone-treated cells, the phosphorylation levels of JAK2 and STAT3 were dose-dependently decreased and p38 and p-ERK signals were notably activated in a dose-dependent manner. Moreover, we found that the addition of S3I-201, a STAT3 inhibitor, led to a decreased expression level of Bcl-2 in Eca109 cells. The chromatin immunoprecipitation assay demonstrated that STAT3 bound to the promoter of Bcl-2 in the Eca109 cells. Furthermore, the mutation of four STAT3 binding sites (-1733/-1723, -1627/-1617, -807/-797, and -134/-124) on the promote of Bcl-2 gene alone attenuated the transcriptional activation of STAT3. In addition, down-regulation of STAT3 resulted less of transcriptional activity of STAT3 on Bcl-2 expression and in a significant reduction in the growth and proliferation of Eca109 cells in vitro. These data provide a potential molecular mechanism of the apoptotic induction function of 2-pyridyl cyclohexanone, and emphasize its important roles as a therapeutic agent for esophageal squamous carcinoma.